2015
DOI: 10.1007/s00228-015-1994-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-response to (statin) therapy: the importance of distinguishing non-responders from non-adherers in pharmacogenetic studies

Abstract: PurposeIn pharmacogenetic research, genetic variation in non-responders and high responders is compared with the aim to identify the genetic loci responsible for this variation in response. However, an important question is whether the non-responders are truly biologically non-responsive or actually non-adherent? Therefore, the aim of this study was to describe, within the PROspective Study of Pravastatin in the Elderly at Risk (PROSPER), characteristics of both non-responders and high responders of statin tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 19 publications
0
29
1
Order By: Relevance
“…However, in many cases where expected response to statin therapy is not observed, poor adherence to therapy or discontinuation of therapy is the usual cause 81 , 82 . Such cases will not be helped by pharmacometabolomics.…”
Section: Existing Examples Of Use Of Metabolomics In Trials and Intermentioning
confidence: 99%
“…However, in many cases where expected response to statin therapy is not observed, poor adherence to therapy or discontinuation of therapy is the usual cause 81 , 82 . Such cases will not be helped by pharmacometabolomics.…”
Section: Existing Examples Of Use Of Metabolomics In Trials and Intermentioning
confidence: 99%
“…As mention in the method section, only 24 out of 120 articles were evaluated by JADAD grading scale and our evaluation resulted in 22 articles with a score of zero (very poor quality), one article with three points and one article that scored 4 as high-quality evidence. [9,10]…”
Section: Resultsmentioning
confidence: 99%
“…[12] In data used from PROSPER study which was a prospective multicenter randomised placebocontrolled trial with JADAD score of 3 showed a significant association of statin-induced myopathy (SIM) with rs2900478 (SLCO1B1) SNPs. [9] In two meta-analysis and one case-control studies, an association was demonstrated between SLCO1B1 c.521T>C polymorphism and statininduced myopathy. [13][14][15] The last two population-based case-control articles in Czech and Japanese population showed no association between SLCO1B1 gene polymorphism and risk of myalgia/myopathy in these two specific population.…”
Section: Slco1b1 Genementioning
confidence: 98%
“…When the outcome of interest has a continuous distribution, sampling individuals from the extremes of the outcome distribution (eg, comparing high with non‐responders in LDL‐C reduction after starting statin treatment) may greatly increase statistical power when faced with budgetary restrictions for genotyping . However, as shown for non‐responders to statin therapy in the PROspective Study of Pravastatin in the Elderly at Risk (PROSPER) trial, issues of treatment non‐adherence are especially important to consider here . This strategy may also be promising when rare variants are investigated, as their prevalence may be greater on the extreme ends of the outcome spectrum …”
Section: Study Designsmentioning
confidence: 99%
“…22 However, as shown for non-responders to statin therapy in the PROspective Study of Pravastatin in the Elderly at Risk (PROSPER) trial, issues of treatment non-adherence are especially important to consider here. 23 This strategy may also be promising when rare variants are investigated, as their prevalence may be greater on the extreme ends of the outcome spectrum. 24 There are some notable challenges in performing case-control studies, the first and foremost being the selection of an appropriate In general, the catchment area for a hospital or clinic is likely to differ for different diseases, which will need to be considered when sampling controls.…”
Section: Outcome-based Designsmentioning
confidence: 99%